Balancing Optimism and Realism: Indonesia’s Urban Youth’s Political Engagement in the 2024 General Elections - P. Bagus Sugiyono; Clara R.P. Ajisuksmo; Teresa Metta Rosario; Yeremias Siane Ikang Soge; Vinsenso Valdis Amor Wijoyo (Faculty of Social Science, Universitas Negeri Malang, 2024)
The discourse around youth political participation often seems pejorative. Many earlier studiescontinue to emphasise youth political apathy, a notion that has long been debunked. Othersreduce urban youth’s political engagement to merely digital activism, largely due to recentinformation and technological advancements. However, this research presents a more nuancedview, arguing that the current political engagement of urban youth is characterised by a balanceof optimism and realism. An online survey of 205 Indonesian youths from various cities wasconducted to gauge their perspectives on political participation, including their views on the 2024general elections. They were asked to examine some sets of statements as descriptions andexplanations of their political stances. The results suggest that urban youth in Indonesia are keento be politically active, including in the 2024 general elections. They stay informed, regularlyfollowing political news and candidate debates, signalling hope for a healthier democracy.However, they remain pragmatic, recognising the flaws in politics, such as corruption, inefficientadministration, and political dynasties, which they view as the “dirty side” of politics. This dualperspective reflects a more complex political stance, where youth are motivated to participate yetgrounded in the reality of the political system’s imperfections.